If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -2) = 5(3x + 1) + 5 Reorder the terms: 7(-2 + x) = 5(3x + 1) + 5 (-2 * 7 + x * 7) = 5(3x + 1) + 5 (-14 + 7x) = 5(3x + 1) + 5 Reorder the terms: -14 + 7x = 5(1 + 3x) + 5 -14 + 7x = (1 * 5 + 3x * 5) + 5 -14 + 7x = (5 + 15x) + 5 Reorder the terms: -14 + 7x = 5 + 5 + 15x Combine like terms: 5 + 5 = 10 -14 + 7x = 10 + 15x Solving -14 + 7x = 10 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -14 + 7x + -15x = 10 + 15x + -15x Combine like terms: 7x + -15x = -8x -14 + -8x = 10 + 15x + -15x Combine like terms: 15x + -15x = 0 -14 + -8x = 10 + 0 -14 + -8x = 10 Add '14' to each side of the equation. -14 + 14 + -8x = 10 + 14 Combine like terms: -14 + 14 = 0 0 + -8x = 10 + 14 -8x = 10 + 14 Combine like terms: 10 + 14 = 24 -8x = 24 Divide each side by '-8'. x = -3 Simplifying x = -3
| 6-2x=6x+10 | | 4(s+3)-1=3(2s+1)+5 | | x^2-308x+23716=0 | | 7a-6=19+2a | | 2x=x+26 | | 4r^2-18r-100=0 | | x+(2x)=12xy*y^2 | | -5(t-3)-(t+4)=10 | | A=2(L+W)(W) | | A=2(L+W) | | 21+(-47)+12+38+(-54)= | | 6y-12y+3= | | X^4-5x^3+11x^2-25x+30=0 | | c=gm | | (2x-3y)(x+2y)=0 | | 6y+12y+3= | | X-5=(2x-3) | | 25r^3-9r=0 | | 8x+9=4x-5 | | 4x+5=6x | | 3y+4z=16(y+z) | | 6v^2-3v+1=0 | | X-5=2(3-x) | | (4x-8)-(7x+9)= | | x-4y=u | | 5=4m+4u | | 7x-35+14=7 | | (4/5)1.175= | | 3x-(5x-4)= | | 3p^4-18p^3-81p^2= | | 1+x-2x+3x-4x=0 | | 3x-4=2(X+5) |